How Organizational Environment Affects Social Responsibility: A Systematic Literature Review and Conceptual Framework From The Perspective of Stakeholder Theory - BEGER, Gizem Aras (International Journal of Contemporary Economics and Administrative Sciences, 2020)
Given that corporate social responsibility (CSR) has been affected by various factors within or around the organization, this study focuses on the interaction of CSR with various environmental dynamics. In Turkish literature, however, this interaction has not been studied comprehensively while organizations’ CSR relationships, especially with their external environment, have remained uncertain. The study first aims to reveal the magnitude of the problem in Turkish literature related to CSR/CSR-environment interactions by reviewing the literature. Second, it seeks possible remedies for overcoming this problem by examining organizations’ relations, especially with their external environment within the scope of stakeholder theory. To achieve these aims, the study firstly provides a systematic literature review (SLR) based on the Ulakbim Social Sciences Database after some discussion about CSR-organizational environment-stakeholder relationships. This relationship landscape is then examined within the context of stakeholder theory through a traditional review of the international literature. From this analysis, a conceptual model is proposed to explain these relationships. Finally, some suggestions are presented for future studies.